1957
DOI: 10.1161/01.cir.15.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Significance of Serum Transaminase Levels in Coronary Occlusive Disease

Abstract: Clinical and experimental studies of acute myocardial infarction suggest that serum glutamic oxalacetic transaminase (SGO-T) levels may have both diagnostic and prognostic significance. The authors report their experience in 255 patients hospitalized because of chest pain strongly suggestive of acute myocardial infarction. The results of serial determinations are compared with the clinical data and the electrocardiographic findings. The data indicate that abnormally high levels have both diagnostic and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1957
1957
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The Chart illustrates the curve obtained in two typical cases when the serum transaminase is plotted against time. These time relationships agree closely with those reported by La and by Kattus et al (1956). The test is most useful in myocardial infarction if a sample can be obtained within a few hours after the onset.…”
Section: Present Investigationsupporting
confidence: 90%
See 1 more Smart Citation
“…The Chart illustrates the curve obtained in two typical cases when the serum transaminase is plotted against time. These time relationships agree closely with those reported by La and by Kattus et al (1956). The test is most useful in myocardial infarction if a sample can be obtained within a few hours after the onset.…”
Section: Present Investigationsupporting
confidence: 90%
“…Thus to the well-established criteria of clinical history and examination, together with the changes in the electrocardiogram, blood sedimentation rate, white-cell count, temperature chart, and urobilinogen excretion, a new biochemical test has been added which helps to determine whether or not recent myocardial infarction has occurred. Since that time several other reports describing increased serum transaminase activity following myocarcfial infarction have been published (Chinsky et al, 1956;Kattus et al, 1956;Merrill et al, 1956).…”
mentioning
confidence: 97%
“…Numerous studies attest to the value of transaminase determination in the recognition of acute myocardial infarction, especially if the level is over 100 units (21,22). Walsh et al (23) have found that pulmonary infarc tion and pneumonia can also produce levels as high, but the rise tends to be slower.…”
mentioning
confidence: 99%
“…In the 1950s, it was noted that certain transaminases were released from dying myocytes and that they could in turn be detected in the laboratory with potential clinical significance for the diagnosis of MI. [1][2][3] This initiated the contest to develop biochemical markers of myocardial damage and to determine their prognostic value. Early markers developed included AST, lactate dehydrogenase (LDH), and the improved creatine kinase (CK) assay in the 1960 s. 4 However, despite the advances, these tests were still limited by specificity to cardiac tissue and a stride forward was made with CK isoenzymes, particularly the MB fraction in 1966.…”
Section: History Of Cardiac Markersmentioning
confidence: 99%